If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 + -1x = 1 + 2x Reorder the terms: 1 + 7x + -1x = 1 + 2x Combine like terms: 7x + -1x = 6x 1 + 6x = 1 + 2x Add '-1' to each side of the equation. 1 + -1 + 6x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 0 + 6x = 1 + -1 + 2x 6x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 6x = 0 + 2x 6x = 2x Solving 6x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6x + -2x = 2x + -2x Combine like terms: 6x + -2x = 4x 4x = 2x + -2x Combine like terms: 2x + -2x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 1/7x^2 | | 11x=2(3x+75) | | 3(2x-2)+6y=0 | | 8(2+5m)=216 | | 8+8k=6k+9 | | 394=5m | | 2(4x-2)=3(2x-1) | | 17x=3(3x+40) | | 2.4*16= | | c^2-5c+2=0 | | -6x+12=-30 | | 4+2(5+(-3))= | | 5x^2=-2-11x | | 72x^3-80x^4= | | 3.25+0.25(v)=14 | | 3y-3+4x-2=3x+3y-1 | | 7p=-5m | | v-4v+10=14 | | b/3-7=_33 | | -5(-2n-4)+5n=-100 | | 4x^2+12=3x | | 36m^3-8= | | 4n+19+3n+28=180 | | 2(−14−2y)/4 | | 3y-1+2y-1-4y=2y+3+y+1 | | -22x+22=x+7 | | -10x+9y=54 | | 6y+26=-7y | | x^2-y-9=0 | | 7.50/123.75 | | 6y+26=-7 | | 26x-13=0 |